ANALISIS KELAYAKAN FINANSIAL PENGUSAHAAN KAYU SENGON (Paraserianthes falcataria) DENGAN POLA TANAM AGROFORESTRY DI KABUPATEN MAGETAN - Dwijo Saputro; Suprapti Supardi; Sri Marwanti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
Sengon (Paraserianthes falcataria) wood is one of the forestry commodities that is currently in demand by farmers in Magetan Regency. Sengon wood business in the community forests is carried out through agroforestry pattern. Agroforestry is a land use (agriculture) that combines forest plants with agricultural crops, which aims to increase profits, both economically as well as environmentally. The research aims to determine the financial feasibility of sengon wood, which is planted through agroforestry patterns. The study was conducted in the Jabung, Ngiliran, and Bedagung Villages, Panekan District, Magetan Regency. Determination of location was done purposively. Primary data collection was carried out through interviews with farmer group members. The financial analysis data used in this research is the 8-year sengon wood cycle. The results of the financial feasibility analysis show that pattern I, which is the combination of sengon tree and clove is more beneficial compared to pattern II, the combination of sengon tree with empon-empon plants. Pattern I is more profitable, since the management costs per ha are lower, while the commodity prices are higher.